Thermal Degradation Kinetics of Polyamide 6,6 Cable Ties by Thermogravimetric Analysis - Rammo, Nabil N.; Mahdi, Hind A. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The thermal degradation of cable ties of polyamide (PA6,6) neat and UV stabilized was investigated by thermogravimetry (TG) and its derivative (DTG) at several heating rates between 5 and 80 oC min-1  in helium atmosphere. High heating rates signal novel peaks in the DTG curves that indicate melting temperature of PA6,6. The kinetic parameters calculated via isoconversion and nonisothermal data using the Flynn-Wall-Ozawa, Kissinger and CoatsRedfern methods showed comparable activation energy values. Exposure of the ties to outdoor environment causes pre-mature stress cracking and brittle failure due to prevalence of crosslinking reaction occurring in the polymer chains